Evaluación de la obtención de celulosa partiendo del buchon de agua (eichhornia crassipes) mediante la hidrólisis básica y el proceso enzimático del hongo pleurotus ostreatus (2019)
The purpose of this research work is to remove the water plug from the El Gualí wetland in order to promote its conservation and thus be able to evaluate the possibility of obtaining cellulose from the water buffer. As a first measure, a pretreatment was carried out on the raw material that consisted in crushing and drying. As a second phase, a preliminary experimental development was carried out to determine parameters such as assembly, concentration and proportion of each of the processes for establish conditions in both the chemical and biological processes respectively.